2020
DOI: 10.1515/zfsoz-2020-0005
|View full text |Cite
|
Sign up to set email alerts
|

Warum wählen Männer und Frauen unterschiedliche Studienfächer?

Abstract: ZusammenfassungTrotz der seit mehreren Jahrzehnten bestehenden geschlechtsspezifischen Unterschiede in der Studienfachwahl, ist es der bisherigen Forschung nur zum Teil gelungen, die zugrundeliegenden Ursachen empirisch herauszuarbeiten und die geschlechtsspezifische Studienfachwahl vollständig zu erklären. Der vorliegende Beitrag geht daher aus verschiedenen interdisziplinären Blickwinkeln der Frage nach, warum Männer und Frauen unterschiedliche Studienfächer wählen und betrachtet hierbei fünf Fächergruppen.D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 77 publications
0
15
0
3
Order By: Relevance
“…In doing so, they consider their strengths in single subjects, such as mathematics or science, but also compare their relative abilities across domains (Jonsson, 1999). Previous research on initial subject choices has demonstrated that individuals use their objective schooling achievements in different domains to assess the probability of succeeding in particular subject groups (Becker et al, 2010;Hägglund & Lörz, 2020;Mann & DiPrete, 2016). Moreover, subjective evaluation of strengths and weaknesses in particular domains seems to matter for the initial subject choice (Hägglund & Lörz, 2020;Mann & DiPrete, 2013;Werfhorst et al, 2003).…”
Section: Theoretical Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In doing so, they consider their strengths in single subjects, such as mathematics or science, but also compare their relative abilities across domains (Jonsson, 1999). Previous research on initial subject choices has demonstrated that individuals use their objective schooling achievements in different domains to assess the probability of succeeding in particular subject groups (Becker et al, 2010;Hägglund & Lörz, 2020;Mann & DiPrete, 2016). Moreover, subjective evaluation of strengths and weaknesses in particular domains seems to matter for the initial subject choice (Hägglund & Lörz, 2020;Mann & DiPrete, 2013;Werfhorst et al, 2003).…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…Previous research on initial subject choices has demonstrated that individuals use their objective schooling achievements in different domains to assess the probability of succeeding in particular subject groups (Becker et al, 2010;Hägglund & Lörz, 2020;Mann & DiPrete, 2016). Moreover, subjective evaluation of strengths and weaknesses in particular domains seems to matter for the initial subject choice (Hägglund & Lörz, 2020;Mann & DiPrete, 2013;Werfhorst et al, 2003). Finally, a large number of studies show that high achievement in secondary school and in higher education decreases the risk of dropping out from higher education (Isleib et al, 2019;Ishphording & Wozny, 2018;Robbins et al, 2004;Wolter et al, 2014).…”
Section: Theoretical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…low risk of unemployment) and the chance of success (e.g. difficulty of the course) (Bieri Buschor et al, 2012; Bieri Buschor et al, 2014; Boudon, 1974; Eccles, 2011; Erikson and Jonsson, 1996; Esser, 1999; Fischer et al, 2019; Gottfredson, 1981; Hägglund and Lörz, 2020; Holland, 1997; Neugebauer, 2013). From this perspective, it is argued that the evaluation of costs and benefits varies according to the individuals’ socioeconomic position (Denzler and Wolter, 2009) and that students from lower educational backgrounds attach greater importance to financial factors when choosing their course of studies (Becker et al, 2010; Lautenbach, 2018).…”
Section: Social Selectivity and Gender-segregation In The Choice Of F...mentioning
confidence: 99%
“…Die Ursachen dieser fachlichkulturellen Berufsvererbung sind weniger gut untersucht. Mit Blick auf die Forschung zu geschlechtsspezifischen Ungleichheiten in der Studienfachwahl könnte die Erklärung aber möglicherweise mit unterschiedlichen Rollenvorbildern im Elternhaus (Busch-Heizmann 2015), Schwerpunktsetzungen in der Schule (Heine et al 2006), leistungsbezogenen Unterschieden ) oder mit einer unterschiedlichen Interessenausbildung zusammenhängen (Ochsenfeld 2016;Hägglund und Lörz 2020). Studien, die sich mit der zeitlichen Veränderung herkunftsspezifischer Unterschiede in der Studienfachwahl auseinandersetzen, liegen in Deutschland bislang nur vereinzelt vor.…”
Section: Forschungsstand Und Theoretische üBerlegungenunclassified